Clay Veins: Their Physical Characteristics. Prediction, and Support - Frank E. Chase (International Conference on Ground Control in Mining, 1984)
Clay veins, also referred to as clay elastic dikes, have been responsible for numerous underground injuries and fatalities. These hazardous structures are also responsible for increased production costs during all phases of mining. For these reasons, the Bureau of Nines has investigated the physical characteristics of and roof instability problems associated with clay veins in order to make support and other mining recommendations. In addition the occurrence and origins of clay veins were examined to determine whether or not the structures could be projected into unmined portions of the coalbed. This investigation included portions of the Arkoma, Illinois, Northern Appalachian, Southern Appalachian, and Uarrior Coal Basins. Virtually a11 clay veins observed or documented occurred in the Illinois and Northern Appalachian Basins. Observed clay veins ranged in sire from 1 inch to 16 feet In cross-section and were found under shale, siltstone, sandstone, and limestone roof rock. Individual clay veins were predominantly composed of claystone; however, limestone. siltstone. and sandstone infilled clay veins do occur. Clay vein formation has been associated with the infilling of fissures which result from compressive, tensile, or shear ground failures. These gaping fissures were propagated by compactional processes and/or tectonic stresses active during and subsequent to coal iff cation. Associated fault, fracture, and slickenside planes commonly parallel clay veins and disrupt the lateral continuity of the immediate and, sometimes, main roof. When clay veins parallel or subparallel the direction of face advance the roof is segmented into cantilever beams causing unstable conditions. Therefore, the strata on either side of the clay vein must be bolted and strapped together to form a beam.